EFEKTIVITAS METODE TUTOR SEBAYA DALAM MENINGKATKAN KETERAMPILAN MEMBUAT DESAIN PAPERTOY MENGGUNAKAN APLIKASI CORELDRAW BAGI SISWA TUNARUNGU - Damri Damri; Ridho Afdillah (INCARE, International Journal of Educational Resources, 2020)
This research begins with the findings of teacher failure in learning skills when teaching students to make paper toy designs. Where the teacher is too focused on teaching one student, causing other students to be less able to make paper toy designs. This study aims to ascertain the teacher's failure and find a way out by increasing the ability to make paper toy designs and increase the social interaction of deaf students. This study uses an experimental method with a Pre-Experimental design. The design used is a single group pretest and posttest. This method is used to see whether the peer tutor method can improve students' skills in making paper toy designs using the Coreldraw application in Perwari Padang SLB. In this study the subject of the study was deaf students of class X in SLB Perwari Padang, amounting to five people. The results of this study indicate that the ability of the paper toy design skills of deaf students to obtain positive results. Based on data processing using the Mann Whitney Test, it was stated that the peer tutoring method was effective in improving paper toy design skills using the Corel Draw application for deaf students at SLB Perwari Padang.